Analysis of Development of Parent Corporations and Foreign Affiliates in Asia in the Period 1992-2008 - Piasecka-Głuszak, Agnieszka (Analiza rozwoju korporacji macierzystych i zagranicznych filii w Azji w latach 1992-2008, 2010)
The development of transnational corporations from Asian countries in the world economy took place at a very fast pace according to data presented by UNCTAD. Number of parent corporations only in Asia during the last seventeen years (1992-2008) increased almost threefold, including also Japan. This article aims to analyze development of Asian parent corporations and foreign affiliates in the period 1992-2008 divided into developed countries which include Japan and developing countries on the basis of numerous reports of the United Nations Conference on Trade and Development.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 91-101
Keywords: development of transnational corporations; transnational corporations and forign affiliates in Asia